The paradox of managerial ownership and financial decisions of the textile sector: An Asian market perspective - Waemustafa, Waeibrorheem (Academic Research Publishing Group, 2018)
The managerial ownership and its impact on financial decisions such as cash holding, and capital structure have been the subject of debate of corporate governance literature. The main objective of this study is to investigate the impact managerial ownership places on financing and cash holding decisions. In addition to that, the currents study is also offering an interesting insight on the issue of simultaneity of financing and cash holding decisions and also will discuss that how the interdependence changes as the level of managerial ownership changes. This study examines the data of 60 companies listed on Pakistan Stock Exchange over the period from 2013 to 2017. To trace the endogeneity, we have employed the Wu Hausman test. It evident from the results that the p-value of both models is significant, which confirms the endogeneity between cash holdings and capital structure decisions. In both models, the managerial the leverage and cash holdings are in positive relation. The MO appears in a non-linear relationship with both cash holding and capital structure decisions of textile firms. The results of the study are also providing support to agency theory, pecking order theory and signaling theory.